Children and television : fifty years of research (Mahwah, N.J. : Lawrence Erlbaum, 2007)
"Children and Television: Fifty Years of Research is a comprehensive review of the literature on children's television, covering fifty years of academic research on children and television. This volume also offers essays by scholars who have been seeking answers to some of the most critical questions addressed by this research. It represents the interdisciplinary nature of research on children and television, and draws on many academic traditions, including communication studies, psychology, sociology, education, economics, and medicine. The bibliography includes studies of content, effects, and policy, and offers research conducted by social scientists and cultural studies scholars. The research questions consider the content of programming, children's responses to television, regulation concerning children's television policies, issues of advertising, and concerns about sex and race stereotyping, often voicing concerns that children's entertainment be held to a higher standard. The bibliography is also included on CD." "This volume will be a required resource for scholars, researchers, and policymakers concerned with issues of children and television, media policy, media literacy and education, and family studies."--BOOK JACKET.
The changing nature of children's television : fifty years of research / Norma Pecora -- From attention to comprehension : how children watch and learn from television / Aletha C. Huston, David S. Bickham, June H. Lee, and John C. Wright -- The impact of television on cognitive development and educational achievement / Marie Evans Schmidt and Daniel R. Anderson -- Television, social roles, and marginality : portrayals of the past and images for the future / Gordon L. Berry -- Is television healthy?: the medical perspective / Michael Rich -- Advertising and consumer development / Nancy A. Jennings and Ellen A. Wartella -- TV violence : research and controversy / John P. Murray -- Health, drugs, and values / Elizabeth P. Lorch.
No system requirements given for CD-ROM.
Keywords: Television and children; Television and youth; Bibliography; Bibliography